A new species of Parasycorax and new records of Sycorax (Diptera: Psychodidae, Sycoracinae) from southern Brazil - Rossito, Lucas; Pinho, Luiz Carlos (Zootaxa, 2019)
Sycoracinae is a subfamily of Psychodidae, currently with 45 extant species (Curler & Jacobson 2012; Santos et al. 2013) classified in three genera: Sycorax Haliday in Curtis; Parasycorax Duckhouse and Aposycorax Duckhouse (Duckhouse 1972; Young 1979). Sycorax comprises a majority of this diversity with 40 extant species, 15 of which are recorded from the Neotropical region (Curler & Jacobson 2012; Santos et al. 2013). Four fossil species of Sycorax have also been described (Curler & Jacobson 2012), including one from middle Miocene Amazonian amber (Petrulevičius et al. 2011). In contrast, Parasycorax includes only four extant species; three from South America and one from the Philippines (Santos et al. 2009) and a fossil species from Cretaceous Burmese amber (Stebner et al. 2015). Here we describe a new species of Parasycorax and provide an updated key to males of all extant and fossil species of the genus. In addition, Sycorax bravoi Santos, Ferreira & Falqueto and Sycorax espiritosantensis Santos & Bravo are recorded for Santa Catarina State, southern Brazil.